FAMILY SUPPORT AND FAMILY ECONOMIC STATUS WITH DEPRESSION LEVEL ON PATIENTS END STAGE RENAL DISEASE (ESRD) IN GATOEL HOSPITAL MOJOKERTO DISTRICT INDONESIA - Abdul Muhith Muhith; Lutfi K; Tatik Sutarti; Hannan Mujib4; Lantin Sulistyorini; Sandu Siyoto (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2019)
Patients with hemodialysis therapy have uncertainty as to how long hemodialysis is required and should accept the fact that therapy is needed throughout life. Because it appears anxiety response, rejection and anger. ESRD patients undergoing hemodialysis therapy, require support from the family. The purpose of this study was to determine the relationship of family support and economic status with depressed ESRD patients who underwent hemodialysis therapy <1 year. The design of this research is descriptive correlation with cross sectional research method, by using simple random sampling technique with the number of samples of 47 ESRD patients who are undergoing hemodialysis at Gatoel Hospital Mojokerto. The Research done in April 2017. The results obtained most of the respondents have economic ability Above the Provincial Minimum Wage of 27 respondents (57.4%). Most of the respondents stated that they received good family support in 30 categories (63,8%) and most of respondents had light depression 24 respondents (51,1%). Based on statistical test of spearman's rho with significance level α 0,05 obtained result (r) = 0,462 meaning bigger than value signifikansi (0,462> 0,05) hence H1 rejected which mean there is no significant relation between economic status with depression level In ESRD patients and Spearman's rho statistical test results obtained significance value 0.000 <0.05 which means there is a significant relationship between family support with depression levels in ESRD patients. The economic level does not affect depression because the cost of hemodialysis therapy all respondents is covered by health insurance, whereas family support has a positive influence where the better the family support the lighter the depression level in ESRD patients undergoing hemodialysis therapy